2022
DOI: 10.1007/s10614-022-10296-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk Connectedness Between Green and Conventional Assets with Portfolio Implications

Abstract: The increasing concerns of investors toward green bonds and their appealing nature of diversification has motivated the current research to study the risk connectedness between green and conventional assets spanning from August 2014 to December 2020. We first estimate the dynamic equi-correlations through DECO-GARCH. Next, we assess the dynamic and static risk connectedness in the median, extreme low, and extreme high quantiles arguing that spillovers vary across different time periods particularly during econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Among the studies with the highest degree of intermediation, the first to be found was the study conducted by [46,47], which contributed to the understanding of the relationship and behavior of green bonds in connection with other financial assets and its impact on portfolio allocation, emphasizing the importance of crisis periods, such as the COVID-19 pandemic, and providing insights for policymakers, investors, and regulatory authorities. The authors in [46,47] highlight the relevance of green bonds in portfolio allocation and risk management strategies, providing insights into their potential diversification benefits, crisis resilience, and evolving role in the investment landscape. It contributes to advancing portfolio theory by incorporating environmental factors and sustainable investment considerations into the portfolio decision-making process.…”
Section: Trunkmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies with the highest degree of intermediation, the first to be found was the study conducted by [46,47], which contributed to the understanding of the relationship and behavior of green bonds in connection with other financial assets and its impact on portfolio allocation, emphasizing the importance of crisis periods, such as the COVID-19 pandemic, and providing insights for policymakers, investors, and regulatory authorities. The authors in [46,47] highlight the relevance of green bonds in portfolio allocation and risk management strategies, providing insights into their potential diversification benefits, crisis resilience, and evolving role in the investment landscape. It contributes to advancing portfolio theory by incorporating environmental factors and sustainable investment considerations into the portfolio decision-making process.…”
Section: Trunkmentioning
confidence: 99%
“…The network analysis reveals the involvement of 247 authors and the formation of 17 links distributed among five clusters. Although these clusters exhibit considerable dispersion, several research co-authorships can be discerned, such as Naeem [47,68], Tiwari [52], Abakah [29,69], Bouri [70,71], and Elsayed [54]. This visual representation offers insights into the existence and characteristics of collaborative networks.…”
Section: Co-author Analysismentioning
confidence: 99%
“…The studies of Karim et al ( 2022a ), Arif et al ( 2021a ), and Liu et al ( 2021a , 2021b ) unveiled various useful features of sustainable, religious, and conventional markets but in an independent market setting. Nguyen et al ( 2020b ) and Naeem and Karim ( 2021 ) also stressed the diversification avenues of green investments against various financial markets. Given the plethora of studies on religious investments, Chowdhury et al ( 2021 ) examined the spillovers among 52 religious stocks and marked positive co-movement between religious stocks and their volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the main reasons that COVID‐19 has transformed the spillovers among financial markets is the high degree of globalization and interconnectedness among different countries' economies (Alawi et al, 2022; Iqbal et al, 2022; Naeem, Karim, & Tiwari, 2022; Naeem, Karim, Uddin, et al, 2022). The pandemic has affected not only public health but also the economies of countries worldwide.…”
Section: Introductionmentioning
confidence: 99%